Tourism guidance tracking and safety platform - Gonçalves, F.; Martins, A. L.; Ferreira, J. C.; Marques, E.; Andrade, M.; Mota, L. (Intelligent Transport Systems: From Research and Development to the Market Uptake. Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2019)
We propose a platform for tourism Guidance Tracking and Safety (GTS) based on beacons Bluetooth Low Energy (BLE), mobile device App and a central cloud server. Context information is provided to improve tourism transportation options taking into account local offer and a collaborative gamiﬁed approach is applied to share trips and advice natural trails walk. Guidance, safety is provided in remote natural walks and a case application in Madeira, island Levadas, natural trails. This work is the results of a submitted project between ICSTE-IUL and Madeira University used to create a tool to get tourism data, advice and orient tourism for ecological trails.